Achievement Of Zvt And Computation Of Its Time Of Occurrence For Power Converters - Foletto Montagner, Vinícius; Leães Hey, Hélio; da Silva Martins, Mário Lúcio; Luís Russi, Jumar (Eletrônica de Potência, 2010)
This paper provides a mathematical expression to determine the occurrence of soft-switching for a general topology of ZVT converters with auxiliary resonant voltage source. This expression is used to help the designer in choosing appropriately the values of inductance and capacitance for the auxiliary resonant branch ensuring ZVT. The main advantage of the proposed methodology is to point out suitable sets of circuit parameters without relying only on time consuming numerical simulations of the entire converter. Additionally, numerical methods to compute the time of occurrence of ZVT for these power converters are provided. The proposed methods are given by second order approximations of a nonlinear function which describes the voltage on the ZVT snubber capacitor during the zero-voltage resonant stage. The results can be seen as applications of second order Taylor series and of quadratic interpolation. However, differently of simply finding the root of a given nonlinear equation, the conditions given here provide analytical expressions to compute the time of occurrence of ZVT based on the converter parameters. Then, the proposed conditions become useful for analysis and design, allowing evaluating operation sequence, total commutation time, resistive losses and other important parameters to describe the converter performance.